Low and High Glycemic Load Diet on Immune Responses of Adolescent Football Athletes (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2021)
High-intensity physical exercise causes physical stress that will suppress immune system in athleteâ€™s body. Decreased immune system function can cause physiological and pathological changes such as fatigue, reduce athlete performance, and increase risk of infection. Regulation diets of glycemic index (GI) and glycemic load (GL) are known to help control blood glucose during exercise so the immune system can be maintained.The purpose of this study was to determine differences effects of low and high glycemic load diets on immune responses in adolescent football athletes. This study was a quasi experimental with multiple time series design, conducted on 22 adolescent football athletes aged 15-17 years old. The subjects were divided into two groups, low GL diet group was given carbohydrate-source foods with GL 9.15, high GL diet group was given foods with GL 27.29. Diet was given once in the morning and 2 hours later subjects doing RAST (Running-based Anaerobic Sprint Test) to trigger physical stress. Immune response was measure using total leukocytes and leukocytes differential count. There were no significant differences in blood glucose levels, leukocyte counts, and leukocytes differential count between low GL and high GL groups (p0.05). Low GL diet causes an increase in blood glucose and total leukocytes smaller than high GL diet.Â